Migrant Networks as a Basis for Social Control : Remittance Obligations among Senegalese in France and Italy - Jean-Noel Senne; Isabelle Chort; Flore Gubert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The economic literature provides much evidence of the positive impacts of social capital on migrants' economic outcomes, in particular through assistance upon arrival and insurance in times of hardship. Yet, although much less documented, migrant networks may well have a great influence on migrants' remittances to their home country and particularly to their origin household. Given all the services provided by the network, the fear of being ostracized by its members and being left with no support system could then provide an additional incentive for migrants to commit to prevailing remittances behavior, as an affirmation of their community membership. In this paper, we thus analyze to what extent migrant networks in the destination country influence the degree to which migrants meet the claims of those left behind. We first develop a simple principal-agent model in which remittances are the result of a contractual agreement between the migrant and his origin household and the network works as an enforcement device. We thus depart from existing models of motives for remitting which generally do not account for the close-knit networks migrants are embedded in. We then use an original data set covering Senegalese migrants residing in France and Italy to test the main predictions of our model.
Keywords: 330